Broca's Area Asymmetry and Language Deficits in Autism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The asymmetry of frontal language cortex in boys with autism, previously reported, was investigated further in a sample of 22 boys with autism compared to 9 boys with specific language impairment (SLI) and 11 normal controls, in a study at Massachusetts General Hospital and Harvard Medical School, Boston.